Manniophyton fulvum extract attenuates sodium nitroprusside induced oxidative stress in wistar rats - Awolayeofori, Dokubo; Obi, Nwaokezi Chris; Nnenna, Okwakpam Felicia (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Sodium nitroprusside (SNP) is an antihypertensive agent. It induces toxicity via the release of cyanide ions, nitric oxide (NO) and reactive oxygen species. Manniophyton fulvum (MF) is commonly used in Nigeria due to its therapeutic and nutritional potentials. This study evaluates the phytochemical composition of aqueous extract of MF root and influence in SNP induced oxidative stress in wistar rats. Methods: Gas chromatography was used for determination of the chemical composition of aqueous extract of MF root. Rat liver homogenate was used for determination of rhodanese, glutathione (GSH) and malondialdehyde (MDA). Twenty (20) adult wistar rats of both sex were randomly divided into 4 different groups comprising 5 animals (n=5). Control (Group A), Groups B, C, D received 2.5 mg/kg body weight of SNP at intervals of 3 hours per day by intraperitoneal injection. In addition, Groups C and D received 200 mg/kg body weight of aqueous root extract of MF and 10 mg/kg body weight of Vitamin E respectively for a period of 7 days. Results: Flavonoids had the highest composition while allicin had the lowest composition. Diallyl thiosulphinate>methyl allyl thiosulphinate >allyl methyl thiosulphinate. The activity of rhodanese, GSH and MDA concentrations showed that Group B had significant (p<0.05) increase in MDA concentration while GSH showed significant (p<0.05) decrease. Also, the activity of rhodanese showed significant (p<0.05) decrease compared to Group A. However, Groups C and D showed significant increase (p<0.05) in the activity of rhodanese enzyme compared to Group A and Group B. GSH levels of Group C and Group D showed no significant (p>0.05) difference while the MDA concentration showed significant (p<0.05) decrease. Correlation analysis between rhodanese and GSH showed strong significant (p=0.01, r=0.894) positive correlation. Conclusions: From this study, it can be deduced that the chemical components of aqueous root extract of MF may serve as a pharmacological agent to up regulate detoxification and cytoprotective enzymes. Aqueous root extract of MF can also induced rhodanese to collaborate with GSH and promote inhibition of lipid peroxidation, anti-oxidative reactions and up regulate cyanide detoxification in tissues.